Method for Detecting Small Aerial Objects Appearing in Field of View in Controlled Part of Celestial Sphere in Infrared Range - F. G. Agayev; H. H. Asadov; G. V. Aliyeva (Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni Kììvsʹkij Polìtehnìčnij Ìnstitut: Serìâ Radìotehnìka, Radìoaparatobuduvannâ)
The article is devoted to the developed method of infrared detection of group remote high-temperature objects. The problem of searching for the extremum of the total infrared radiation of a group of non-identical thermal objects carrying out a group flight is formulated and solved using the variational optimization method. Examples of such objects include the flight of aircraft in a group, ground scenes involving a group of objects of interest, temperature diagnostics of various points of buildings, control of automobile traffic on highways, control of group flights of birds, drones, etc. A condition has been determined under which the total value of the infrared radiation flux of thermal elements in the group reaches an extreme value. The regression relationship function between the emission coefficient of the thermal elements of the group and the atmospheric transmission coefficient has been calculated. The problem of optimal control of small thermal objects randomly distributed in the atmosphere is practically solved using a ground-based multi-radar system in which elements of a multi-radar system monitor flying objects with different values of the radiation coefficient on the routes and different atmospheric transparencies. The proposed method can be used for remote control of flight or the functioning of a group of flying thermal objects with different values of the radiation coefficient with a special procedure for selecting a controlled aircraft for observation by an element of a multi-radar system. The property of the extremum of the total IR radiation flux was found in the inverse relationship between the radiation coefficients of all controlled flying objects and the transparency of the atmosphere along the route between the multi-radar element and the controlled flying object.